2020
DOI: 10.3390/molecules25225299
|View full text |Cite
|
Sign up to set email alerts
|

Combination Antitumor Effect of Sorafenib via Calcium-Dependent Deactivation of Focal Adhesion Kinase Targeting Colorectal Cancer Cells

Abstract: Sorafenib has been recently used for the treatment of patients with advanced colorectal cancer (CRC) and is recognized for its therapeutic value. However, the continuous use of sorafenib may cause resistance in the treatment of cancer patients. In this study, we investigated whether sorafenib exerts an enhanced anticancer effect on CRC cells via the calcium-mediated deactivation of the focal adhesion kinase (FAK) signaling pathways. The appropriate dose of sorafenib and lactate calcium salt (CaLa) for a combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Recent studies based on the molecularly targeted drugs Bevacizumab, Cetuximab and Sorafenib have been used for treating CRC. These drugs have improved the overall survival rate of CRC patients ( Garcia et al, 2020 ; Jeong et al, 2020 ; Giordano et al, 2021 ). However, not all patients, especially the ones with advanced and distant metastases, benefit from these targeted drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies based on the molecularly targeted drugs Bevacizumab, Cetuximab and Sorafenib have been used for treating CRC. These drugs have improved the overall survival rate of CRC patients ( Garcia et al, 2020 ; Jeong et al, 2020 ; Giordano et al, 2021 ). However, not all patients, especially the ones with advanced and distant metastases, benefit from these targeted drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that maintained Ca 2+ influx can destroy the components of FAK’s focal connections in the presence of Src deficiency, markedly inhibiting cell invasion and motility ( Jeong et al, 2020 ). We further investigated whether RB altered intracellular Ca 2+ levels to suppress the Src/FAK/Paxillin focal adhesion pathway, thereby inhibiting the invasion of GBM cells.…”
Section: Resultsmentioning
confidence: 99%
“…There is strong evidence of calcium-dependent suppression of cancer cell proliferation and migration by So, which occurs due to deactivation of FAK (focal adhesion kinase) and inhibition of Akt signaling. For example, the addition of lactate calcium salt to colorectal cancer cells causes an increase in [Ca 2+ ] i , which correlates with the inhibition of the above signaling pathways [ 39 ]. The continuous influx of Ca 2+ ions into the cytosol is one of the mechanisms of apoptosis activation due to calcium-dependent activation of proteolytic and catabolic degradation enzymes (proteases and phosphatases) [ 40 ].…”
Section: Discussionmentioning
confidence: 99%